2021
DOI: 10.1186/s12891-021-04631-9
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral fracture as a risk factor for self-harm: a retrospective cohort study

Abstract: Background The prevention of self-harm is an international public health priority. It is vital to identify at-risk populations, particularly as self-harm is a risk factor for suicide. This study aims to examine the risk of self-harm in people with vertebral fractures. Methods Retrospective cohort study. Patients with vertebral fracture were identified within the Clinical Practice Research Datalink and matched to patients without fracture by sex and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“… 13 , 14 , 20 Of the studies reporting osteoporosis, three reported suicidal ideation as the outcome, 18 – 20 and five reported suicide as the outcome. 11 , 13 , 14 , 21 , 22 Of the studies examining fractures, two reported the outcome of self-harm, 23 , 26 two of suicidal ideation, 15 , 20 six of suicide, 13 , 14 , 24 28 and one included the outcome of self-harm and suicide. 26 In the three studies examining both population groups of osteoporosis and fractures, one reported the outcome suicidal ideation 20 and two reported on the risk of suicide ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… 13 , 14 , 20 Of the studies reporting osteoporosis, three reported suicidal ideation as the outcome, 18 – 20 and five reported suicide as the outcome. 11 , 13 , 14 , 21 , 22 Of the studies examining fractures, two reported the outcome of self-harm, 23 , 26 two of suicidal ideation, 15 , 20 six of suicide, 13 , 14 , 24 28 and one included the outcome of self-harm and suicide. 26 In the three studies examining both population groups of osteoporosis and fractures, one reported the outcome suicidal ideation 20 and two reported on the risk of suicide ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“… 13 , 14 Most studies included a relatively even sample of male and female participants, but only three stratified risk estimates by sex. 13 , 19 , 23 The majority of studies showed moderate to high risk of bias (Supplementary Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations